Poppy and Max and the noisy night - Grindley, Sally; Gardiner, Lindsey (London : Orchard Books, 2008)
Poppy and Max begin to hear strange noises in the house when they try to settle down to sleep.
"Orchard colour crunchies"--Cover p. [4].
2.1
K-3
Keywords: Dogs -- Juvenile fiction; Noise -- Juvenile fiction; Sleep -- Juvenile fiction; Dogs -- Fiction; Noise -- Fiction; Sleep -- Fiction; Dogs -- Fiction; Noise -- Fiction; Sleep -- Fiction